Development and initial validation of the Adolescent and Adult Mindfulness Scale (AAMS). (1st March 2018) - Droutman, Vita; Golub, Ilana; Oganesyan, Ani; Read, Stephen
Abstract: This paper presents five studies describing the creation and validation of a Mindfulness scale that is developmentally appropriate for children 11 and older and also suitable for use with adults. The Adolescent and Adult Mindfulness Scale (AAMS) scale measures key components of mindfulness: (1) focus on the present moment, represented by paying attention to surroundings, thoughts, feelings and emotions, (2) being non-reactive, (3) being non-judgmental, and (4) self-accepting. Study 1 describes the original scale creation: item selection, initial validation and item reduction using exploratory factor analysis and initial validation using confirmatory factor analysis (CFA). This study also investigates the correlation of the AAMS with a previously validated mindfulness scale for children. Studies 2 and 3 validate the scale finalized in Study 1, on an early and mid-adolescent samples. Study 4 validates the scale on an adult sample. Study 5 evaluates scale sensitivity to change in mindfulness due to mindfulness training and examines its relationships with emotion regulation and self-compassion scales. CFA demonstrated a good fit of the factor structure with both adolescents and adults. The AAMS is the only scale available that is validated on such a wide range of ages from early teens to adults. Highlights: Developmentally appropriate for adolescents 11 and older and suitable for adults The only mindfulness scale for children and teens with multi-factor structure Measures focus on the present, being non-reactive, non-judgmental, self-accepting CFA demonstrated a good fit of the factor structure with all age groups. The only scale that is validated on a wide range of ages from early teens to adults